A optimizing the role of community leaders in the prevention and control of diabetes during the COVID-19 pandemic - Emy Leonita; Nopriadi Nopriadi (Jurnal Pengabdian Kesehatan Komunitas, 2021)
Indonesia is ranked 6th in the world for the number of people with diabetes. The current condition of the Covid-19 pandemic is barriers to the management of diabetes in all cities in Indonesia, as well as in Pekanbaru City, so that people are limited in getting health services. One of the efforts needed for diabetes management is health education. Health education targeting community leaders aims to increase the knowledge of community leaders about the management and prevention of diabetes complications so that they become role models in positive behavior change. Health education was carried out in Pekanbaru City to 30 community leaders. The methods used in education are online and offline lectures, discussions and health checks for participants. The result of the activity was an increase in the knowledge of community leaders in implementing diabetes prevention and control efforts during the Covid-19 pandemic. Therefore, community leaders were able to mobilize community members in preventing the incidence and complications of diabetes. The development and trainning for role of the community leaders in diabetes management in a planned manner needs to be carried out continuously to support the success of the program. ABSTRAK Indonesia menduduki peringkat ke-6 di dunia untuk jumlah penderita diabetes. Kondisi pandemic Covid-19 saat ini menghambat penatalaksanaan penyakit diabetes di seluruh kota di Indonesia, demikian pula di Kota Pekanbaru, sehingga masyarakat terbatas mendapatkan pelayanan kesehatan. Salah satu upaya yang diperlukan untuk penatalaksanaan diabetes adalah edukasi kesehatan. Edukasi kesehatan dengan sasaran tokoh masyarakat bertujuan untuk meningkatkan pengetahuan tokoh masyarakat tentang penatalaksanaan dan pencegahan komplikasi diabetes sehingga menjadi role model dalam perubahan perilaku positif. Edukasi kesehatan dilaksanakan di Kota Pekanbaru kepada 30 orang tokoh masyarakat. Metode yang digunakan dalam edukasi adalah metode ceramah secara online dan offline, diskusi dan pemeriksaan kesehatan bagi peserta. Hasil kegiatan adalah meningkatnya pengetahuan tokoh masyarakat dalam menerapkan upaya pencegahan dan pengendalian diabetes pada masa pandemi Covid-19, sehingga tokoh masyarakat mampu menggerakkan anggota masyarakat dalam mencegah kejadian maupun komplikasi diabetes. Pengembangan dan pembinaan peran tokoh masyarakat dalam pengelolaan diabetes secara terencana, terus menerus perlu dilaksanakan untuk menunjang keberhasilan program.